Assessing Students' Writing and Public Speaking Self-Efficacy in a Composition and Communication Course - Terrell K. Frey; Jessalyn I. Vallade (Central States Communication Association, 2018)
One avenue for assessing learning involves evaluating self-efficacy, as this psychological beliefis a strong predictor of academic achievement. As such, the purpose of this study was to evaluate writing self-efficacy and public speaking self-efficacy in a composition and communication course. This course is structured to develop both writing and public speaking competencies; the research sought to determine whether students believed they were leaving the course feeling more confident in their capabilities within each respective academic domain. Results (N= 380) from pre- and post-test data suggest that students' reported writing and public speaking self-efficacy significantly increased over the semester. Additionally, students' mastery experiences, operationalized as informative essay and informative speech grades, were related positively to changes in self-efficacy at the end of the semester. These results offer three implications for teaching within this course design and structure.